2019
DOI: 10.1176/appi.ps.201800482
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Psychoeducation and a Text Messaging Adherence Intervention Among Individuals With Hypertension and Bipolar Disorder

Abstract: Objective: This study evaluated the feasibility, acceptability, and preliminary efficacy of psychoeducation plus an automated text-messaging intervention (iTAB-CV) to improve adherence for antihypertensives and bipolar disorder medication. Methods: Following a psychoeducation program, iTAB-CV was administered for two months. In month one, participants received one educational/motivational and one mood rating text daily. In month two, medication reminders were added. Results: The sample (n=38) was 74% African-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…In a 2018 retrospective study, published outside the date range for this review, analyses showed patients newly initiated on antipsychotic medication who were fully adherent (PDC ≥80%) for ≥6 months had significantly lower adjusted rates of psychiatric hospitalization (6.0%) compared to those who were partially adherent (8.3%, PDC ≥40% and <80%) or nonadherent (8.8%, PDC <40%). 48 To this end, building upon interventions targeted to other factors associated with nonadherence, such as simplifying medication regimens, 38 , 49 , 50 programming medication reminders, 44 , 51 and programs to strengthen the patient-clinician therapeutic alliance 5 , 6 , 44 need to be a research priority as well as part of ongoing clinical management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2018 retrospective study, published outside the date range for this review, analyses showed patients newly initiated on antipsychotic medication who were fully adherent (PDC ≥80%) for ≥6 months had significantly lower adjusted rates of psychiatric hospitalization (6.0%) compared to those who were partially adherent (8.3%, PDC ≥40% and <80%) or nonadherent (8.8%, PDC <40%). 48 To this end, building upon interventions targeted to other factors associated with nonadherence, such as simplifying medication regimens, 38 , 49 , 50 programming medication reminders, 44 , 51 and programs to strengthen the patient-clinician therapeutic alliance 5 , 6 , 44 need to be a research priority as well as part of ongoing clinical management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by research conducted by (Hadidi, 2016) proving that psychoeducation has a significant effect on reducing systole and diastole. This is supported by research conducted by (Levin et al, 2019) proving that giving psycho-education can improve the compliance of hypertensive patients in doing therapy and can reduce blood pressure. Several studies have shown that the management of hypertension with a non-pharmacological therapeutic approach including weight loss, alcohol, sodium and tobacco restriction, exercise and relaxation are mandatory interventions that must be performed on each therapy in hypertension patients (Smeltzer & Bare, 2014).…”
Section: Blood Pressurementioning
confidence: 87%
“…A recent large clinical trial demonstrated limited long-term adherence advantage for passive medication aids (e.g., 7-day pill organizer, pill cap displaying time since last dose), a category into which eCAP TM would fall [65]. Experience with eCAP TM in a pilot BD and hypertension adherence study [66] conducted by members of the study team yielded substantially less missing data using the eCAP TM than the Medication Event Monitoring System (MEMS) [32]. Adding an extra financial incentive for bringing in the eCAP TM or scanning it using the free eCAP TM app on the participant's phone ($10 per visit) optimizes use of automated pill monitoring.…”
Section: Primary Outcomementioning
confidence: 99%
“…Adding an extra financial incentive for bringing in the eCAP TM or scanning it using the free eCAP TM app on the participant's phone ($10 per visit) optimizes use of automated pill monitoring. Notably, in the previously mentioned iTAB-CV R21 project using eCAPs TM , 31/38 participants (81.6%) brought their eCAP TM to all 3 study visits over a 6-month period [66]. To optimize generalizability, individuals who use medisets or pillminders to manage multiple medications will not be excluded from the study.…”
Section: Primary Outcomementioning
confidence: 99%